Evaluation of the anti-spasmodic activity of essential oils of Ammodaucus leucotrichus fruits and its main chemical component “perillaldehyde” on intestinal smooth muscle contractions of rodents: ex vivo and in silico approaches - Karim, Ahmed; Marghich, Mohamed; Amrani, Ouafa; Addous, Abdelhay; Malek, Sanae; Beyi, Leila; Harit, Tarik; Aldisi, Dara; Aboul-Soud, Mourad A. M.; Giesy, John P.; Aziz, Mohammed (Frontiers in Chemistry, 2024)
Ethnopharmacological relevanceIn Moroccan traditional medicine, plants from the Apiaceae family are widely utilized in folk medicine to treat various diseases associated with the digestive system. Ammodaucus leucotrichus plays an important role as an antispasmodic that has been traditionally used, especially to treat digestive tract diseases in children.Aim of the studyThe aim of this research was to verify the traditional use by assessing the relaxant and spasmolytic activities of A. leucotrichus essential oil (ALEO) and then comparing them to the effects and potency of the major constituent of ALEO, which is perillaldehyde.Materials and methodsThe in vitro evaluation of ALEO’s relaxant and spasmolytic effects was carried out on isolated rats and rabbit jejunum in an organ bath setup. Intestinal contractility was recorded using an isotonic transducer connected to an amplifier. GC/MS analysis was conducted to identify components within ALEO. Subsequently, these compounds underwent in silico absorption, toxicity, and molecular docking studies.ResultsGC/MS analysis of this essential oil studied revealed seven compounds, which account for 98.67% of the oil, with the dominance of two compounds, namely, perillaldehyde (91.12%) and limonene (6.33%). ALEO and its main compound, perillaldehyde, reversibly relaxed the basal tone of rabbit jejunum, with the IC50 values 158.68 ± 13.89 and 95.03 ± 0.93 μg/mL, respectively. Moreover, ALEO caused a dose-dependent spasmolytic effect on Carbachol (CCh) and KCl provoked jejunum contraction in rats. Furthermore, the decrease in contractions of pre-contracted jejunum by CCh was more pronounced for perillaldehyde compared to ALEO, with an IC50 value of 68.59 ± 6.57 μg/mL, which was half compared to that of ALEO. The pre-treatment of the tissue with concentrations ranging from 30 to 100 μg/mL caused a rightward and downward shift in the concentration–response curves for CaCl2 and CCh. These results suggest that the spasmolytic effect of ALEO is mediated possibly through a non-competitive antagonist of calcium channel or muscarinic receptors. Our results are confirmed by the fact that perillaldehyde exhibited the highest docking scores on muscarinic acetylcholine receptors (M2 and M3) and voltage-gated calcium channels, with D-limonene showing lower binding energies in comparison. These remarks confirm that the activity of ALEO is attributed to the presence of perillaldehyde. In addition, perillaldehyde exhibits a low degree of in silico acute toxicity and high percent of intestinal absorption.ConclusionIn summary, ALEO exhibits myorelaxant and antispasmodic effects by inhibiting muscarinic receptors and calcium channels, which can be attributed to the presence of perillaldehyde. This provides a scientific foundation for the traditional use of A. leucotrichus in treating gastrointestinal disorders and opens up possibilities for developing a more effective and less toxic drug-utilizing perillaldehyde.